Zn–HA–TiO2 nanocomposite coatings electrodeposited on a NiTi shape memory alloy. (2nd December 2014) - Mirak, Mohammad; Alizadeh, Morteza; Salahinejad, Erfan; Amini, Rasool
<x xml:space="preserve">Abstract</x> In this work, zinc–hydroxyapatite (Zn–HA) and zinc–hydroxyapatite–titania (Zn–HA–TiO2) nanocomposite coatings were electrodeposited onto a NiTi shape memory alloy, using a chloride zinc plating bath. The structure of the composite coatings was characterized by X‐ray diffraction, scanning electron microscopy and high‐resolution transmission electron microscopy. According to the results, the Zn–HA–TiO2 coating exhibited a plate‐like surface morphology, where the addition of the nanoparticles caused to an increase in roughness. It was also found that due to applying a proper stirring procedure during co‐deposition, a homogenous dispersion of the nanoparticles in the coatings was achieved. Also, the addition of the TiO2 nanoparticles to the Zn–HA–TiO2 coating enhanced the microhardness and wear resistance. Copyright © 2014 John Wiley & Sons, Ltd.